2020
DOI: 10.1186/s12974-020-01764-x
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 exerts anti-inflammatory effects and regulates NLRX1-TRAF6 via SHP-1 in stroke

Abstract: Background: Acute inflammation induced by reactive astrocytes after cerebral ischemia/reperfusion (I/R) injury is important for protecting the resultant lesion. Our previous study demonstrated that DJ-1 is abundantly expressed in reactive astrocytes after cerebral I/R injury. Here, we show that DJ-1 negatively regulates the inflammatory response by facilitating the interaction between SHP-1 and TRAF6, thereby inducing the dissociation of NLRX1 from TRAF6. Methods: We used oxygen-glucose deprivation/reoxygenati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Then dehydrated with increasing concentrations of alcohol. After transparentized by xylene for 3 min, sealed with neutral resin ( Peng et al, 2020 ). All the sections were assessed the pathological changes by a microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then dehydrated with increasing concentrations of alcohol. After transparentized by xylene for 3 min, sealed with neutral resin ( Peng et al, 2020 ). All the sections were assessed the pathological changes by a microscope.…”
Section: Methodsmentioning
confidence: 99%
“…As a multifunctional protein, DJ-1 is involved in a variety of signal transduction pathways, including those associated with antioxidative stress, free radical scavenging and mitochondrial homeostasis ( Repici and Giorgini, 2019 ). Our previous study showed that DJ-1 negatively regulated cerebral I/R inflammatory responses by promoting SHP-1 and TRAF6 interactions ( Peng et al, 2020 ). Researchers hypothesized that DJ-1-deficient microglia exhibited increased cytotoxicity by promoting the secretion of the proinflammatory cytokines IL-1β and IL-6 ( Trudler et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of NLRX1 in inflammation-associated diseases is also supported by a number of literature data. For example, NLRX1 alleviates hypoxia-induced apoptosis and inflammation during acute myocardial infarction [ 98 ], or acts as an anti-inflammatory agent in cerebral ischemia reperfusion injury via decreasing pro-inflammatory cytokine production [ 99 ]. Furthermore, NLRX1 deficiency leads to exacerbated LPS-induced heart injury by enhancing NF-κB and NLRP3 inflammasome activation [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study had highlighted the protein DJ‐1 (PARK7 and GATD2) in regulating CNS inflammation by NF‐κB signalling 110,111 . Recently, Peng et al 112 discovered this DJ‐1‐mediated regulation of inflammation is dependent on NLRX1 and an interactor protein SHP1. The authors use an oxygen–glucose deprivation IR model in primary astrocytes, as well as an in vivo cerebral occlusion model to assess the relationship of DJ‐1, SHP1 and NLRX1.…”
Section: Nlrx1 In Diseasementioning
confidence: 99%